The Role of State Government Policies and Infrastructure Development in Promoting Sustainable Religious Tourism: A Moderated Analysis of Cultural Diversity - Shrestha, Purna Man; Kathayat, Bhupal Bikram (PYC Nepal Journal of Management, 2023)
This study examines the role of state government policies and infrastructure development on the promotion of sustainable religious tourism. This study employed an inferential research design to assess the general and moderating effects of the latent variables of the study. Quantitative methods were used for robust analysis, and 404 participants, including both domestic and international tourists and visitors with diverse religious beliefs, were selected through convenience sampling. Data were collected using a survey questionnaire. The study reveals that state government policy positively impacts promotion of sustainable religious tourism, whereas infrastructure development does not have any significant effect. Furthermore, there is a notable positive relationship between cultural diversity and promotion of sustainable religious tourism. In addition, cultural diversity moderates the relationship between state government policies and sustainable religious tourism. However, no such moderating found in the relationship between infrastructure development and sustainable religious tourism. However, this paper has not incorporated other factors which have significance influence on the promotion of sustainable religious tourism; policymaker can implement the findings of this paper to formulate the policy related to the promotion of sustainable religious tourism.